2021
DOI: 10.3390/pr9020339
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Analysis of Optimization Techniques for Integrated Energy Systems Utilizing Renewable Energy Sources: A Review for CHP and CCHP Systems

Abstract: Energy generation and its utilization is bound to increase in the following years resulting in accelerating depletion of fossil fuels, and consequently, undeniable damages to our environment. Over the past decade, despite significant efforts in renewable energy realization and developments for electricity generation, carbon dioxide emissions have been increasing rapidly. This is due to the fact that there is a need to go beyond the power sector and target energy generation in an integrated manner. In this rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 171 publications
(161 reference statements)
0
8
0
Order By: Relevance
“…In addition, the discharge temperature does not change fuel consumption and therefore does not affect emissions. Rezania et al [64] study a variety of optimization methods that can improve the performance of integrated energy systems (IES), especially heat and combined energy (CHP) and cooling, heating, and combined energy (CCHP), using renewable energy sources; also it is shown by specifying the characteristics of each method along with accurate statistical reports. The results showed that classical optimization methods are no longer efficient for integrated energy systems and CHP, and innovative and modern optimization methods have been replaced.…”
Section: Chp From An Economic Perspectivementioning
confidence: 99%
“…In addition, the discharge temperature does not change fuel consumption and therefore does not affect emissions. Rezania et al [64] study a variety of optimization methods that can improve the performance of integrated energy systems (IES), especially heat and combined energy (CHP) and cooling, heating, and combined energy (CCHP), using renewable energy sources; also it is shown by specifying the characteristics of each method along with accurate statistical reports. The results showed that classical optimization methods are no longer efficient for integrated energy systems and CHP, and innovative and modern optimization methods have been replaced.…”
Section: Chp From An Economic Perspectivementioning
confidence: 99%
“…Given that practical viability was one of the primary objectives, cost allocation for gasification and ORC systems was based on operational plants or the existing units in the market. In this context, the Gothenburg Biogas Gasification project located in Sweden [41], and the Scharnhauser Park ORC project located in Germany [42] were considered as the reference systems for unit cost allocation (investment, operating, and maintenance), development cost calculation, and fuel price estimation for the two proposed configurations; this was carried out using Equations ( 17)- (30).…”
Section: Economic Incentives and Environmental Policiesmentioning
confidence: 99%
“…For the application considered, a fluidized-bed gasifier was the best option since the possibility of up-scaling within a wide power range is provided [29]. In comparison with the fixed-bed technology, changes in fuel characteristics are more tolerable since the ratio of biomass to oxygen can be varied independently to maintain the temperature uniform throughout the bed [30]. The major drawback of such a compact and economic arrangement is the contamination of syngas with nitrogen, tars, and particles which drastically reduces the heating value of gaseous fuel.…”
Section: Biomass Gasificationmentioning
confidence: 99%
“…The characteristics of requirements elicitation are described in several ways, namely collaborative (stakeholder expertise), observational (system understanding and knowledge) and contextual (user requirements) [15][16], contextual (user requirements) [17][18]. The elicitation techniques are classified into brainstorming, workshops, Joint Application Development (JAD), group work, ethnography, introspection and user scenarios [19][20].…”
Section: Charateristics Of Requirements Elicitationmentioning
confidence: 99%